(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Developing countries have depended since long time on the developed countries to increase the levels of development and improving rates of growth direction to the best way where taking this dependence many shapes influenced by the evolution form of international relations and this dependence shows how the great deficiencies in sources of local financing, which called developing countries to increase their reliance on external funding sources, represented in the form of grants, subsidies, loans and foreign investment, pursuing States in that the application of economic reform policies in pursuit of faster economic growth and restructure its economy and achieve economic stability. In the early eighties of the last century and with the escalation of the debt crisis in developing countries, including Egypt and the accompanying of default and shake international confidence in the large number of developing countries and the high cost of external borrowing have been a lot of developing countries to pressure by the international organizations (the International Monetary Fund and the World Bank), so it has tended Egypt and most Countries to open their economic to foreign direct investment as an alternative to external funding sources.